Externalities of Waste Dis-amenities, Benefit Transfer Application on Piyungan and Putri Cempo Landfill, Indonesia - Evi Gravitiani; Aulia Hapsari Juwita (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2020)
Waste is a national problem in Indonesia. It is related to the old paradigm of waste management, which is only collected, transported, and disposed to the landfill. The same problem occurs in some big cities in Java. Landfills use open dumps, and that causes an increase in negative externalities in the quality of the environment for people who live nearby. This study aims to analyze the externalities of the Piyungan landfill. The objects of this research are the people who lived around the dump. Cost of illness and replacement cost are analysis tools to calculate the externalities. Benefit transfer is used to analyze the externalities ofthe Putri Cempo landfill in Surakarta. The benefit transfer method was developed as an alternative way to value externalities using values from studies of similar circumstances, carried out at related sites somewhere else, given the challenges and high costs inherent in assessing the actual price. Accurately, to test the performance of the benefit transfer method, this study focused on estimates of externalities associated with waste dis-amenities. The results indicate that the existence of the Piyungan landfill has a negative influence on the economic and social aspects as well as the environment of the people around it. It also happens in the Putri Cempo Landfill.